Fashion Sebagai Identitas Pada Komunitas Punk di Semarang - Rayhan Ferdiyanto, Rakha; Budi Lestari, Sri (Interaksi Online, 2021)
Fashion is one of the ways a person communicates, where fashion can reflect the wearer, however, this is the case with punk followers. Punk uses fashion as their way of communicating messages to the public. As a counter-culture or counter-culture to the dominant culture, punk fights against all establishment shown by the dominant culture through a "different" style of dress. However, as time went on, the punk community in line with this was reported negatively, as well as the implementation of misconceptions of meaning by elements in punk who committed negative actions, so that the name of punk in Indonesia was getting worse, especially in Semarang City. This study aims to describe the motives of the punk community in fashion, and how they interpret the fashion worn by using qualitative research methods. This research shows the critical paradigm with a qualitative descriptive approach. The data technique used in this study was in-depth interviews with 3 informants. The theory used in this research is the shared culture theory put forward by Mark Orbe. The results of the study indicate that the three informants have their own motives in dressing punk, namely selling, and being accepted by their respective groups. Likewise with what they mean in the punk fashion they wear, namely, self-expression, positive resistance and music. So that it is found that they have no intention of fighting against the establishment or other negative things. Through co-cultural theory, it can also illustrate that the punk community in Semarang does not have the desire or aim to disturb public order. Instead, they often make various efforts such as charity and voluntary collection of goods to be given to people in need. These things are done by them with the aim of being accepted by the community